Hubungan Tingkat Stres dengan Perubahan Pola Menstruasi pada Remaja - Pande Putu Novi Ekajayanti; Pande Putu Indah Purnamayanthi (PLACENTUM: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2020)
Background: Adolescence is a transition period in the span of human life that connects childhood and adulthood. One disorder experienced by adolescents is stress. At this time, there are many facts that reveal the relationship between stress and menstrual changes that are a health problem for women. This correlational study aims to determine the relationship of stress levels to changes in menstrual patterns in teenagers.Subjects and Method: The study used a cross sectional research design. The subjects of the study were all 92 class IX young women in SMP Negeri 2 Denpasar. The sampling technique was purposive sampling. Data collection using a questionnaire. Statistical analysis using the Chi-Square Test.Results: The results showed that there was a relationship between stress levels and changes in menstrual patterns in teenagers with p (value) of 0.01 and α = 0.05.Conclusion: There is a relation between stress levels and changes in menstrual patterns.